The role of artificial intelligence in generating Arabic neologisms: A study of gaming localization - Hammouri, Dina M (Research Journal in Advanced Humanities, 2025)
This study examines the use of Arabic neologisms in the Arab gaming community. It analyzes Personal Computer (PC) and console games such as Fortnite, Call of Duty, and Minecraft to shed light on the application of Artificial Intelligence (AI). It focuses on introducing, promoting, and determining Arabized neologisms in gaming terminology. The study shows the nature and size of this linguistic transformation, as well as the types of word-formation processes which contribute to it. The data for this research were collected from two sources: (1) the responses of 400 school and university (undergraduate and postgraduate) students to a limited set of questions. (2) live and interactive conversational exchange with the gaming community.  The study shows that gamers use these neologisms for practicality and convenience, accuracy and relevance, trendiness and internationalization, and the lack of equivalence in the Arabic language system. Further, the following processes, which mark the integration of neologisms into the Arabic language system, are identified namely, loan blends, syntactic changes, morpho-syntactic changes, phonemic changes, abbreviations, and clipping.  This study aims to provide an understanding of how contemporary language, particularly in the AI gaming community, is modified and to serve as a template for future research.